2016
DOI: 10.18632/oncotarget.8918
|View full text |Cite
|
Sign up to set email alerts
|

IDH-1R132H mutation status in diffuse glioma patients: implications for classification

Abstract: WHO2007 grading of diffuse gliomas in adults is well-established. However, IDH mutations make classification of gliomas according to the WHO2007 edition controversial. Here, we characterized IDH-1R132H mut status in a cohort of 670 adult patients with different WHO2007 grades of diffuse glioma. Patient characteristics, clinical data and prognoses were obtained from medical records. Patients with IDH-1R132H mut were younger and had better clinical outcomes than those without mutations. Differences in age among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
7
12
0
Order By: Relevance
“…Immunohistochemistry was used for detection of IDH mutations. The procedures were performed as described previously [ 9 ] using primary antibodies against IDH1 R132H (Dianova 1:100) . The cutoff values were 10% for IDH-1 R132H mut .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was used for detection of IDH mutations. The procedures were performed as described previously [ 9 ] using primary antibodies against IDH1 R132H (Dianova 1:100) . The cutoff values were 10% for IDH-1 R132H mut .…”
Section: Methodsmentioning
confidence: 99%
“…The discovery that isocitrate dehydrogenase (IDH) mutations are more common in sGBMs was one of the most significant advancements in the understanding of gliomas [ 3 , 4 ]. Patients with glioblastomas carrying IDH mutations or wildtype IDH, exhibited large differences in prognosis, age, and genetic alternations [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunohistochemistry was performed as we did previously. [ 12 ] Immunostaining of GH and PRL was positive (Fig Supplement 1), suggesting a PRL-GH secreting plurihormonal tumor. Next, the tumor sample obtained from the operation was used to evaluate the PD-L1 expression and CD8 + lymphocytes infiltration in the tumor tissues.…”
Section: Case Reportmentioning
confidence: 99%
“…Additionally, in vitro studies have strongly suggested that the altered expression of lncRNAs during genome mutation or genotoxic stress is involved in multiple neuro-oncological disorder-associated cellular processes. Isocitrate dehydrogenase 1 (IDH1) mutations have been shown to be an important prognostic marker for patients with gliomas ( Cai et al, 2016 ; Wang P.F. et al, 2016 ).…”
Section: Profile Of Lncrnas In Human Glioma Research and Therapymentioning
confidence: 99%